DESAIN BUKU ILUSTRASI ALAT MUSIK JAWA TENGAH UNTUK PAUD NGESTI RAHAYU UNGARAN - D., Zahra Aunurahma; Mujiyono, Mujiyono (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Traditional Javanese musical instruments such as gamelan are cultural heritage that has educational and aesthetic value. These instruments not only produce distinctive sounds, but also contain cultural meanings that are important to be introduced to children from an early age. However, nowadays children are more familiar with popular culture and the lack of visual learning media that introduces local culture in an interesting way causes a low interest in traditional musical instruments. The design of this illustration book aims to introduce traditional Central Javanese musical instruments to the children of preschool Ngesti Rahayu in Ungaran as a fun educational medium. This design uses a descriptive visual approach and an educational thematic. This book was developed through several stages of manual sketching, digitization, and layout. The work is in the form of a book measuring 20 x 20 cm with illustrations in the form of musical instruments in the form of saron, kenong, text, girls. The book consists of a front back cover, introduction, main content,. All gamelan is presented objectively in a simplification style through red to yellow. This book not only introduces the form and way of playing the instrument, but also reinforces the values of the local culture.